"Implementasi Model Dzikrullah Berbasis Tarekat melalui Riyadhah dalam Pembelajaran Pendidikan Agama Islam" - Ali, Muhamad Mauris Faruqi; Syahidin, Syahidin (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
This study aims to examine the implementation of the tarekat-based dzikrullah model through the riyadhah approach in learning Islamic Religious Education (PAI) as a strategy to deepen spirituality and strengthen Islamic character in the midst of the challenges of the materialistic and secular modern era. This study uses a literature study method by analyzing theories and concepts from various sources related to the practice of dzikrullah, tarekat, and riyadhah, as well as their impact in the context of education. The results of the study show that the dzikrullah model which is carried out consistently through the approach of tarekat and riyadhah plays a significant role in improving the spiritual quality of students. This model is effective in creating a conducive learning environment, solemn, and focuses on the development of religious values. In addition, this approach also contributes to the formation of noble morals and spiritual discipline of students, which has a positive impact on their daily lives.